Sex-specific maladaptive responses to acute stress upon in utero THC exposure are mediated by dopamine - Serra Valeria; Traccis Francesco; Aroni Sonia; Vidal Palencia Laura; Concas Luca; Serra Marcello; Leone Roberta; Porcu Patrizia; Busquets Garcia Arnau; Frau Roberto; Melis Miriam (Pharmacological Research)
Cannabis remains by far the most consumed illicit drug in Europe. The availability of more potent cannabis has raised concerns regarding the enhanced health risks associated with its use, particularly among pregnant women. Growing evidence shows that cannabis use during pregnancy increases the risks of child psychopathology. We have previously shown that only male rat offspring prenatally exposed to Δ9-tetrahydrocannabinol (THC), a rat model of prenatal cannabinoid exposure (PCE), display a hyperdopaminergic phenotype associated with a differential susceptibility to acute THC- and stress-mediated effects on sensorimotor gating functions. Here, we explore the contribution of the hypothalamic-pituitary-adrenal (HPA) axis, key regulator of body adaptive stress responses, to the detrimental effects of acute stress on ventral tegmental area (VTA) dopamine neurons and sensorimotor gating function of PCE rats. We report a sex-dependent compromised balance in mRNA levels of genes encoding mineralocorticoid and glucocorticoid receptors in the VTA, alongside with stress-induced pre-pulse inhibition (PPI) impairment. Notably, VTA dopamine neuronal activity is causally linked to the manifestation of stress-dependent deterioration of PPI. Finally, pharmacological manipulations targeting glycogen-synthase-kinase-3-β signaling during postnatal development correct these stress-induced, sex-specific and dopamine-dependent disruption of PPI. Collectively, these results highlight the critical sex-dependent interplay between HPA axis and dopamine system in the regulation of sensorimotor gating functions in rats.